Nanoscale manipulation of the Mott insulating state coupled to charge order in 1T-TaS2 - Doohee Cho (Nature Portfolio, 2016)
Controlled switching between states in materials with strong electronic correlations can form the basis for functional devices. Here, the authors use a scanning tunnelling microscope tip to switch between a Mott insulator state and a metallic state with charge-density-wave domains in 1T-TaS2.